A STUDY ON THE BACTERIAL DISSEMINATION AND EXPERIMENTAL PATHOLOGY OF SALMONELLA PARATYPHI - B INFECTION IN WHITE MICE - Al-Joboury, Khalil H. (The Iraqi Journal of Veterinary Medicine, 2000)
An attempt to simulate paratyphoid fever-B, in the experimental animals has been carried out in white mice. Paratyphoid bacilli type-B was isolated from the febrile patients in the Ibn-Al-Khatib hospital. One LD50 was enough to produce disease in the white mice, however 10 doses were used for mice. The microorganism was inoculated intraperitoneally in to the experimental animals; the course of the dissemination within the animals was clarified by sacrificing two mice at specific intervals after inoculation and for 30 days. The organs of the sacrificed and dead mice were examined for the presence ofmicroorganisms. The microorganism were found in the spleen, liver and mediastinal lymph node for 29,25 and 17 days postinfection respectively, whereas, the microorganisms were persist in the lungs and heart blood for 11 days and in the brain and kidneys for 7 days postinoculation. The pathological changes were initiated as a neutrophils aggregates and microabscesses in the spleen, liver and mediastinal lymph node. During the second week post infection, these microabscesses and neutrophils aggregates will be replaced by mononuclear cells (lymphocytes and macrophages) to form granulomatous type lesion in these organs and to become more chronic and fibrosed, during third and fourth week post-infection. Also mild miscellaneous pathological lesions were demonstrated during the first week in brain kidney and in the lungs and gradually disappeared.